Digital Village Transformation: A Human Resource Readiness Perspective - Permatasari, Marisa; Khair, Otti Ilham (Universitas Muhammadiyah Ponorogo, 2026)
Digital village represents the implementation of digital transformation at the rural level, aimed at improving public services, efficiency, and accountability. This research aims to examine human resource readiness and efforts to improve it. The research was conducted using a qualitative approach. Data collection was carried out through interviews with participants from the Ciawi Village government. Data analysis utilized the People Capability Maturity Model. The research findings revealed that at level 2 (Managed), the Ciawi Village government does not yet have sufficient readiness to face digital village transformation. Based on the process areas of the People Capability Maturity Model, several areas require attention, specifically work environment, performance management, and training and development. The Ciawi Village government needs to develop its physical work environment to enhance community services and support village officials productivity. It needs to consider performance management to identify areas requiring development. This creates its relevancy with training and development programs to ensure alignment with digital transformation needs. The limitation of this research was that it specifically analyzed the readiness of Ciawi Village’s human resources aspect in facing the digital village transformation; it did not consider the readiness of any other aspects such as digital infrastructure and digital literacy. Future research will emphasize on digital literacy of the village community, broadening the scope of the digital village transformation readiness analysis.